Qualitative Analysis of Adulterant Mixed in Different Food Stuffs - Kharel, Prabhat; Sapkota, Anita; Regmi, Pallavee; Subba, Bimala; Sharma, Khaga Raj (Journal of Nepal Biotechnology Association, 2024)
This study focuses on identifying adulterants present in items such as food, fuels, chemicals and cosmetics, known for degrading their overall quality. The escalating concern over food adulteration prompted this research, emphasizing the detection of adulterants in daily consumables. The detrimental effects of food adulteration are profound, leading to health issues such as cancers (colon and peptic ulcer diseases), chronic liver diseases, electrolyte imbalance, kidney failure, heart diseases, blood disorders, and bone marrow abnormalities. The primary objective of this research is to ensure the quality of commonly consumed food items by detecting potential adulterants. Numerous rapid detection techniques have been developed to address this problem, including the implementation of quick and straightforward DART methods (Detect Adulterant Rapid Test). In this study, we applied various DART and DIY methods to test selected food items like milk, turmeric powder, and chilli powder. Each sample underwent testing with specific chemical reagents to determine the presence of adulterants. Post-tests, the samples were analyzed for observable changes, and conclusions were drawn regarding the presence or absence of adulterants in each tested item.